1980
DOI: 10.1111/j.1365-2044.1980.tb03952.x
|View full text |Cite
|
Sign up to set email alerts
|

Administration of drugs during cardiopulmonary bypass

Abstract: Summary This study was conducted to determine the efficiency of delivery of drugs injected as holuses by the common

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
3

Year Published

1983
1983
1999
1999

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 12 publications
1
3
0
3
Order By: Relevance
“…Rouby et al (16) have shown, in patients with artificial hearts, a significantly greater decrease in SVR with propofol than with thiopental, falling to nearly 50% of the basal value 5 min after administration of the drug. Likewise, in a study similar to ours but with no control group, Baraka et al ( 1 7) showed a decrease in the MAP following propofol administration during CPB which is comparable in coronary and valvular patients, and which cannot be Table 2 Hemodynamic values prior to (basal) and I , 3,5,10,15,20 and 30 min after administration of 0.9% saline solution (control, n = 10) or 2 mg. kg-' propofol (n = 10) during cardiopulmonary bypass. attributed to decreases in the venous return.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Rouby et al (16) have shown, in patients with artificial hearts, a significantly greater decrease in SVR with propofol than with thiopental, falling to nearly 50% of the basal value 5 min after administration of the drug. Likewise, in a study similar to ours but with no control group, Baraka et al ( 1 7) showed a decrease in the MAP following propofol administration during CPB which is comparable in coronary and valvular patients, and which cannot be Table 2 Hemodynamic values prior to (basal) and I , 3,5,10,15,20 and 30 min after administration of 0.9% saline solution (control, n = 10) or 2 mg. kg-' propofol (n = 10) during cardiopulmonary bypass. attributed to decreases in the venous return.…”
Section: Discussionsupporting
confidence: 55%
“…This reduction in the afterload of the left ventricle, with the consequent decrease in the ventricular work that it produces (5, 6), partially counteracts the negative inotropic effects of the drug that have been demonstrated in both animals (19) and humans (10). During CPB, the most reliable route for administration of drugs is through the pump oxygenator venous reservoir (20). However, the oleic nature of propofol, due to its solvent, impeded its rapid and homogeneous mixture with the oxygenator blood in this study and explains the appearance of a "supernatant" for some time after its administration.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Estes podem se ligar competitivamente às proteínas plasmáticas e promover o deslocamento do fármaco do sítio de ligação, aumentando temporariamente a sua concentração plasmática. Além disso, a administração da protamina reverte a anticoagulação da heparina; portanto a protamina restringe o efeito desse antitrombótico na extensão da ligação do propofol à albumina plasmática (KAMATH et al, 1980;METS, 2000;WOOD, 1979).…”
Section: Discussionunclassified
“…Em Após a retirada das cânulas vasculares, procede-se à reversão da anticoagulação promovida pela heparina com a protamina (KAMATH et al, 1980;METS, 2000).…”
Section: Circulação Extracorpórea (Cec-h)unclassified